On Rydberg excitons in two-dimensional semiconductors - Hoang, Ngoc Cam; Nguyen, Nhu Dat; Duong, Thi Man; Pham, Thi Bich Thao; Nguyen-Truong, Hieu (Communications in Physics, 2025)
We study Rydberg excitons in two-dimensional transition-metal dichalcogenide semiconductors, using the Rytova-Keldysh potential to account for nonlocal dielectric screening effects. We determine exciton binding energies in monolayer WSe\(_2\) and WS\(_2\) by the variational method. We perform calculations for different dielectric environments (isolation, hBN encapsulation, and SiO\(_2\) substrate support) to investigate the influences of the surrounding dielectric environment. Our theoretical results agree reasonably with experimental measurements and previous numerical calculations. The study shows a strong dependence of exciton binding energy and spatial extent on both the principal and angular quantum numbers, as well as on the surrounding dielectric environment.